Blood and coagulation product disposition in the modern era: An international multicenter survey endorsed by the European Association of Cardiothoracic Anesthesiology and Intensive Care (EACTAIC) - Gerber, Daniel; Bolliger, Daniel; Agarwal, Seema; Zulauf, Fabio; Erdoes, Gabor (Frontiers in Anesthesiology, 2022)
Study Objective: Perioperative transfusion is associated with reduced survival and increased morbidity and mortality. Several studies report wide variation in clinical transfusion practice. However, the influence of simple, practical factors - such as which blood products are available, and when - is often disregarded. We hypothesized that these practical issues are relevant confounders of transfusion decisions. Design: Web-based survey Setting: Multi-institutional Participants: Members of the European Association of Cardiothoracic Anaesthesiology and Intensive Care (EACTAIC) society reached by monthly newsletter in November 2020. Interventions: No interventions Measurements: Survey responses Main results: The newsletter was opened by 429 members. We collected 51 complete surveys, resulting in a response rate of 11.9%. 72% of participants reported having a local algorithm for the use of blood products and coagulation factors. Latency in the time of blood product delivery / availability and the possibility to store or return unused products were most often reported as having an influence on transfusion practice. For point-of-care test availability, 86% of addressees reported rotational thromboelastometry / -elastography, 76% hemoglobin tests, 24% international normalized ratio (INR) measurement and 22% platelet function testing. Six percent of the respondents did not have access to point-of-care tests. The majority of addressees reported that they were able to obtain more than 10 allogeneic blood products simultaneously (63%). Packed red blood cells were available with a delay of 10-15 minutes and platelets with a delay of 15-20 minutes. Conclusions: Our survey indicates a wide variability in the logistics of perioperative transfusion practice. The information gained could provide a solid basis for future improvements of the guidelines, but also in local transfusion practices.